Clinical Encounters in Sexuality: Psychoanalytic Practice and Queer Theory - Giffney, Noreen; Watson, Eve (punctum books, 2017)
Clinical Encounters in Sexuality makes an intervention into the fields of clinical psychoanalysis and sexuality studies, in an effort to think about a range of issues relating to sexuality from a clinical psychoanalytic perspective. This book concentrates on a number of concepts, namely identity, desire, pleasure, perversion, ethics and discourse. The editors, Noreen Giffney and Eve Watson, have chosen queer theory, a sub-field of sexuality studies, as an interlocutor for the clinical contributors, because it is at the forefront of theoretical considerations of sexuality, as well as being both reliant upon and suspicious of psychoanalysis as a clinical practice and discourse. The book brings together a number of psychoanalytic schools of thought and clinical approaches, which are sometimes at odds with one another and thus tend not to engage in dialogue about divisive theoretical concepts and matters of clinical technique. Traditions represented here include: Freudian, Kleinian, Independent, Lacanian, Jungian, and Relational. The volume also stages, for the first time, a sustained clinical psychoanalytic engagement with queer theory. By virtue of its editorial design, this book aims to foster a self-reflective attitude in clinical readers about sexuality which historically has tended toward reification